2000
DOI: 10.1088/0029-5515/40/4/301
|View full text |Cite
|
Sign up to set email alerts
|

Fast ion relaxation and confinement in the gas dynamic trap

Abstract: Studies of the relaxation and confinement of hot anisotropic ions are considered to be the key elements of the gas dynamic trap (GDT) experimental research programme. The method of confinement study described consists essentially in the comparison of measured ion parameters with those predicted by computer simulations. To realize this approach a set of diagnostics for the measurements of local and global parameters of the fast ions has been developed. In particular, this set includes diagnostics to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 15 publications
7
19
0
Order By: Relevance
“…We estimated the average energy of the beam-produced deuterons to be about 10 keV. The measured angular width of fast ion distribution and their energy distribution well correspond to the results of numerical simulations [7]. We also found that the heated target plasma losses are dominated by the axial ones through the mirrors, as predicted.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…We estimated the average energy of the beam-produced deuterons to be about 10 keV. The measured angular width of fast ion distribution and their energy distribution well correspond to the results of numerical simulations [7]. We also found that the heated target plasma losses are dominated by the axial ones through the mirrors, as predicted.…”
supporting
confidence: 82%
“…At the end of beam injection pulse, the ion temperature was close to that of the electrons. The parameters of the fast ions were measured by using an artificial target method [7], neutral particle analyzers, and an array of diamagnetic loops installed at different axial locations inside the solenoid [8]. We estimated the average energy of the beam-produced deuterons to be about 10 keV.…”
mentioning
confidence: 99%
“…Neutrons are born as a result of thermonuclear reactions between energetic deuterium ions driven by neutral beam injection (NBI); the energy confinement time of fast ions is determined by the electron-ion Coulomb collisions, 2 / 3 e h T   . For this reason, the electron temperature is the main factor limiting the confinement time of fast ions and, thus, the power efficiency of a beam-driven fusion reactor 13 . Success in ECRH experiments at GDT is convincing enough to consider the prospects of simple axially symmetric open magnetic traps as a high-power neutron source for a number of fusion applications 14 , including material testing, a hybrid fusion-fission reactor and nuclear waste processing 12,[15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…The GENESYS calculation results have been compared with the results presented in [15,16]. Particularly, comparison with the warm plasma components temperature, angular width of the fast ions distribution function, the fast plasma energy content and the 1D neutron emission rate depending on the machine axis position was carried out.…”
Section: Neutron Source Simulationmentioning
confidence: 99%